Optimization and application of blasting parameters based on the ＂pushing-wall＂ mechanism - Ren, Feng-yu; Sow, Thierno Amadou Mouctar; He, Rong-xing; Liu, Xin-rui (International journal of minerals, metallurgy and materials, 2012)
The large structure parameter of a sublevel caving method was used in Beiminghe iron mine. The ores were generally lower than the medium hardness and easy to be driUed and blasted. However, the questions of boulder yield, ＂pushing-wall＂ accident rate, and brow damage rate were not effectively controlled in practical blasting. The model test of a similar material shows that the charge concentration of bottom blastholes in the sector is too high; the pushing wall is the fundamental reason for the poor blasting effect. One of the main methods to adjust the explosive distribution is to increase the length of charged blastholes. Therefore, the field tests with respect to increasing the length of uncharged blastholes were made in 12# stope of-95 subsection and 6# stope of Beiminghe iron mine. This paper took the test result of 12# stope as an example to analyze the impact of charge structure on blasting effect and design an appropriate blasting parameter that is to similar to No. 12 stope.